A comparative study between dexmedetomidine and maxtures of midazolam and morphine for postoperative sedation in intensive care unit - Mohamad, Azlina (2005)
Introduction: The a.2 agonist · dexmedetomidine is a new sedative and analgesic agent which is licensed in the USA for post-operative intensive care sedation. We compared dexmedetomidine with the mixture of midazolam and morphine for post-operative patient who required mechanical ventilation in intensive care unit (ICU). Objedive: To compare the effect of dexmedetomidine and midazolam-morphine mixture among post-operative patients in ICU; in term of the amount of analgesic (PCA morphine) requirement, s~dation score, haemodynamic profiles and time of extubation. Methodology: Prospective, double-blinded randomized controlled trial study design involved post-operative patients admitted to the Intensive Care Unit {ICU) of Hospital Universiti Sains Malaysia (HUSM) conducted from June 2003 to June 2004. Thirty-four mechanically ventilated post-operative patients were randomly assigned to receive short-term (minimum 4 hours) sedation with either continuous intravenous infusion of dexrnedetomidine (group Dex, n=17) or midazolam-morphine mixture (group MM, n=17). Both groups received similar intraoperative anaesthetic regime. Patient controlled analgesia (PCA Morphine) was given to patient as rescue analgesic. Analgesic (PCA morphine) used (mg/hour), Ramsay sedation scoring, extubation time (minute), systolic blood pressure, diastolic blood pressure, mean arterial pressure and heart rate were Medical Sciences, Universiti s.ains Malaysia had approved this study on 9th April 2003. Result: Mean extubation time of dexmedetomidine group was significantly lower than midazolam and morphine mixture group [mean {s.d.): 40.3 ± 16.5 minutes versus 57.9 ± 17.7 minutes, p=O.OS]. Within the first 4 hours drug infusion, mean systolic blood pressure [mean (s.d.): 105 ± ·14 mmHg vs 127 ± 24 mmHg, (p=O.OOO)], mean diastolic blood pressure [mean {s.d.): 59± 8mmHg vs 66 ± 13 mmHg (p=O.OOO)], mean arterial pressure [mean {s.d.): 76 ± 9 mmHg vs 86 ± 15 mmHg (p=O.OOO)] and mean heart rate [mean (s.d.): 88 ± 13 beats per minute vs 102 ± 24 beats per minute (p=O.OOO)] were significantly lower in dexmedetomidine group than tho!?e in midazolam and morphine mixture. There was significant difference of mean Ramsay sedation score between dexmedetomidine and midazolam morphine mixture {p=O.OOO). However, there was no significant difference of mean dose of morphine per hour between dexmedetomidine groups and midazolam morphine mixture [(mean (s.d.); 1.4 ± 0.7 mglhour) versus mean (s.d.}; 1.1 ± 0.8 mg/hour), p= 0.157 ]. Conclusion: Dexmedetomidine provides safe, effective sedation and analgesia for postoperative long surgical patient in intensive care unit. Haemodynamic variables of dexmedetomidine group was more stable than midazolam and morphine mixtures group. Thus dexmedetomidine provides better perioperative haemodynamic control for a _long surgery. The use of d~xmedetomidine also allowed for more rapid tracheal extubation.